Olfactory Neuroblastoma and Olfactory Ventricle: A Case Report. Issue 4 (August 2014) - Pozzati, Eugenio; Martinoni, Matteo; Marucci, Gianluca; Bacci, Antonella
A case of dumbbell nasal and intracerebral olfactory neuroblastoma (ONB) related to possible seeding through an "olfactory ventricle" in the olfactory bulb and nerve is reported. This anatomic variant was recognized at operation for the first time: it consists of a hollow cavity within the olfactory bulb and nerve which may be connected to the subventricular zone of the frontal horn of the lateral ventricle. Better scrutiny of this structure is necessary in view of its possible interference with the course and diffusion of ONBs.